Inspiromatic‐safety and efficacy study of a new generation dry powder inhaler in asthmatic children. Issue 10 (15th June 2018) - Steuer, Guy; Prais, Dario; Mussaffi, Huda; Mei‐Zahav, Meir; Bar‐On, Ophir; Levine, Hagit; Gendler, Yulia; Blau, Hannah; Stafler, Patrick
Abstract: Background: Dry powder inhalers (DPI) are effective but forceful inhalation required to fluidize the powder may be difficult for children and patients with airway disease. Inspiromatic is a new generation active DPI that actively suspends drugs in synchrony with inhalation. We evaluated safety and efficacy of Formoterol delivery via Inspiromatic, compared to Aerolizer, a conventional DPI, in pediatric asthmatic subjects. Methods: A phase I/II, randomized, single‐center, double‐blind, double‐dummy, placebo‐controlled, cross‐over study. Subjects aged 8‐18 years with FEV1 40‐80% predicted were included. Patients were randomized to inhale Formoterol via the Inspiromatic, immediately followed by the placebo via the Aerolizer or vice versa, in a double‐blind fashion. Spirometry, blood pressure, and heart rate were measured at baseline and 15, 30, and 60 min after drug administration. Capsule emptying, comfort of use, confidence in efficacy, and patient satisfaction were assessed. At a subsequent visit, three months later, patients inhaled the active drug via the other DPI. Results: Twenty‐nine patients, aged 12.6 (±2.3) years, mean (SD), completed the study. Baseline FEV1 was 69.1 (±6.7) % at visit one and 65.3 (±9) % at visit two. Maximal FEV1 increase was 16.6 (±7.1) % with Inspiromatic and 15.5 (±7.5) % with Aerolizer ( P  = 0.47). No differences in heart rate or blood pressure were observed; 24/28 capsules were emptied using the Inspiromatic and 19/28 with the Aerolizer ( P  = 0.5); 21/28 preferred the Inspiromatic and 7/28 the Aerolizer ( P  < 0.001). There were no adverse events. Conclusions: Formoterol inhalation via the Inspiromatic is safe and as efficacious as with the Aerolizer. The device is well accepted by asthmatic subjects.